Cash Waqf and Its Importance in Activating Waqf Role in Indonesia | وقف النقود وأهميته في تفعيل دور الوقف في إندونيسيا - Yuli Yasin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2015)
This article describes the legality of cash waqf, privileges, and its urgency in managing and developing waqf in the Islamic world in general, following fiqhiyah actual problems associated with the practice of cash waqf. Specifically article discusses the importance of cash waqf in managing and developing waqf assets in Indonesia.